Interactive Learning Media-Oriented Educational Games Scratch to Increase Interest in Learning Science in Fourth Grade Elementary School Students - Komang Ridja Kamandewi; Desak Putu Parmiti; Kadek Edi Yudiana (Universitas Pendidikan Ganesha, 2025)
This study was motivated by the problem of low learning interest among fourth-grade elementary school students in Natural and Social Sciences (IPAS) lessons. The aim of this research is to describe the effectiveness of interactive instructional media oriented toward educational games using Scratch to increase students’ interest in IPAS subjects. The study employed the ADDIE development model with a Research and Development (R&D) approach, involving a limited trial with fourth-grade elementary students aged 10–11 years. The research design used was a one-group pre-test post-test design to measure changes in learning interest before and after the intervention. The results showed that interactive learning media based on educational games using Scratch had a significant effect on improving students’ interest in learning IPAS, specifically on the topic “My Indonesia Rich in Culture.” The implication of this research is that Scratch-based learning media provide opportunities for students to actively participate, be creative, and become more motivated in the learning process, making it a promising and innovative alternative for teachers in designing more engaging and effective IPAS lessons for elementary school students.